Basarabia ca prefață, cuprins, rezumat și concluzie a unei vieți trăite sub patru regimuri - Nicolae ENCIU (Dialogica: Revistă de Studii Culturale și Literatură, 2021)
Representing a praise brought to the distinguished architect Alexandru Budișteanu, the given approach presents the architect’s reflections on the four socio-political systems in which he had lived and activated. Alexandru Budișteanu declares himself a nationalist and a patriot. Ethnically, the architect is a Romanian from Bessarabia. Alexandru Budișteanu was born in Bălți in 1928, but had to take refuge in Romania in 1944, where, from 1977 to 1983, he served as Chief Architect of Bucharest. As a memorialist, he edited two autobiographical volumes: Between History and the Judgment of Posterity (2010), consisting of a series of dialogues between historian and publicist Flori Bălănescu and the architect himself, and Under Four Regimes on All Continents (2014), which describes chronologically the four political regimes. Thanks to these works, the period of communist domination becomes accessible not only to researchers, but also to the large public, to future generations.